Transcriptome profiling of the whitefly Bemisia tabaci reveals stage‐specific gene expression signatures for thiamethoxam resistance. Issue 5 (29th July 2013) - Yang, N.; Xie, W.; Jones, C.M.; Bass, C.; Jiao, X.; Yang, X.; Liu, B.; Li, R.; Zhang, Y.
Abstract: Bemisia tabaci has developed high levels of resistance to many insecticides including the neonicotinoids and there is strong evidence that for some compounds resistance is stage‐specific. To investigate the molecular basis of B. tabaci resistance to the neonicotinoid thiamethoxam we used a custom whitefly microarray to compare gene expression in the egg, nymph and adult stages of a thiamethoxam‐resistant strain (TH‐R) with a susceptible strain (TH‐S). Gene ontology and bioinformatic analyses revealed that in all life stages many of the differentially expressed transcripts encoded enzymes involved in metabolic processes and/or metabolism of xenobiotics. Several of these are candidate resistance genes and include the cytochrome P450 CYP6CM1, which has been shown to confer resistance to several neonicotinoids previously, a P450 belonging to the Cytochrome P450s 4 family and a glutathione S‐transferase (GST) belonging to the sigma class. Finally several ATP‐binding cassette transporters of the ABCG subfamily were highly over‐expressed in the adult stage of the TH‐R strain and may play a role in resistance by active efflux. Here, we evaluated both common and stage‐specific gene expression signatures and identified several candidate resistance genes that may underlie B. tabaci resistance to thiamethoxam.